RATIONALE OF THE SYNERGETIC APPROACH IN THE RESEARCH OF THE ADMINISTRATIVE AND LEGAL SUPPORT OF SERVICE AND COMBAT ACTIVITIES OF THE NATIONAL GUARD OF UKRAINE - Korniyenko, D. (Honor and Law, 2020)
The issue of substantiation of the synergistic approach in the study of the administrative and legal support of military service of the National Guard of Ukraine has been updated. The purpose of the article is to study modern scientific research on the use of a synergistic approach and substantiation of the appropriate approach in the study of the administrative and legal support of military service of the National Guard of Ukraine. It is established that the development of modern scientific thought shows that the application of a synergistic approach in the study of problematic issues in any sphere of social activity provides the most effective results. Therefore, it is proposed to apply this approach in the study of the administrative and legal support of military service of the National Guard of Ukraine. The essence of science synergetics is covered. It is determined that from the point of view of fundamental science, synergetics is one of the paradigms of modern natural science. The direction of activity of synergetics is to search for the general patterns of evolution and the self-formation of natural, social and cognitive systems, that is, it forms the basis for understanding the new world. However, at the same time, it can be considered being a way of thinking of modern science - one of the important paradigms. Therefore, synergetics is inclined to philosophy by its meaning, according to the description of self-organizing systems it exists as a theoretical and methodological approach. Existing approaches to the application of the synergistic approach in the study of legal science are investigated. Synergetics has been proven to be a methodology of legal knowledge that considers the legal sphere of society and its elements as large, complex open, uneven, nonlinear dynamic systems that have feedbacks and exist only under conditions of constant energy exchange, namely information with external environment. As a result, synergetics sets the task of researching the self-organization of law in order to predict possible scenarios of its evolution and prevent its degradation. The main provisions of the science of synergetics in the study of the administrative and legal support of military service of the National Guard of Ukraine are determined. It is substantiated that the scientific approach with the use of synergetic ideas allows developing a qualitatively new group of methods and principles of research in legal support. Synergistic ideas can help "unleash" important reserves to increase the efficiency of legal regulation of military service of the National Guard of Ukraine without significant expense, and, importantly, minimize the cost of limited legal means and ways. The directions of the further scientific researches will be directed to the research of administrative and legal support of military service of National Guard of Ukraine.